Islamic Religious Education (PAI) Learning In The Society 5.0 Era To Improve Critical Thinking Skills - Hayati, Aziza Nur; Raharjo, Raharjo; Ikhrom, Ikhrom (Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia., 2024)
The development of technology, information, and communication requires people in the era of Society 5.0 to have various life skills. One such skill is critical thinking skills. Critical thinking skills are useful for minimizing the occurrence of various negative impacts of technological advances. In addition, people who have critical thinking skills will easily solve various problems in life. This study aims to determine the implementation of Islamic Religious Education (PAI) learning in the era of Society 5.0, evaluate critical thinking skills, and analyze the implications of Islamic Religious Education (PAI) learning in the era of Society 5.0 in improving critical thinking skills. This research uses qualitative methods with questionnaire instruments, observation and interview guidelines, and documentation. The results showed that: 1) in the era of society 5.0, PAI teachers use a problem-based contextual learning model, utilize technology as a learning medium, and encourage students to actively seek information from various sources, 2) students' critical thinking skills are in a good category, 84% of students already have critical thinking skills in the medium and high categories, 3) Islamic Religious Education (PAI) learning in the era of society 5.0 has implications for skills critical thinking.